Islamic Feminist Interpretation: A Reformulation of the Universal-Particular - Afifi, Mahmoud (Universitas Islam Internasional Indonesia, 2022)
This article examines the trend of Islamic Feminist interpretation by analysing the thought of two leading Muslim feminists i.e. Amina Wadud and Asma Barlas. The selection of Wadud and Barlas is based on the fact that their works articulate a full-blown theory of Islamic feminist hermeneutics, with bearings on theology, philosophy, experience, and more importantly, language. Additionally, both feminists have produced significant revisions of their earlier works on Qur'ānic hermeneutics. Their revisions feature evolutions of their earlier ideas, as well as responses to critiques of their feminist readings of the Qur'ān. This article explores Wadud's and Barlas's reformulation of the hermeneutic binary of 'the universal and the particular' and the extent to which this binary is part of the formation of the two authors' hermeneutics. In this regard, the article aims to investigate their intellectual efforts in developing a hermeneutic theory centered on the Qur’an as God’s speech. By studying the universal-particular binary in the works of both authors, this article argues that Wadud's and Barlas's ambivalent position on the sacredness of the Qur’ān has inhibited their hermeneutic enterprise from developing a sensitive approach to mainstream Muslim belief regarding the Qur’ān as God’s unchanging word, hence carrying the stigma of an un-authoritative discourse among lay Muslims.